Health literacy of adolescents’ responses to a workshop focusing on food, nutrition, climate change and digital technology solutions in Oceania: a multi-site pilot study in Vanuatu - Louisa R. Peralta; Rowena Forsyth; Nanise Lapi; Krestina L. Amon; Pierre Metsan; Guillaume Wattelez; Juliana Chen; Olivier Galy; Corinne Caillaud (BMC Public Health)
Abstract Background Non-communicable diseases (NCD) have become the leading cause of premature death and disability in the Pacific region, with the development of health literacy an important factor for the prevention and control of NCD. Health literacy is an important lifelong asset that can be developed in adolescents through engagement in schooling and curriculum. The aim of this study was to explore Ni-Van adolescents' health literacy knowledge and capabilities regarding food and nutrition, climate change and digital technology solutions. Methods Two Ni-Van schools participated in the study (one urban (School A) and one rural school (School B)), with 44 students (68% female) comprising 14 small groups participating in one workshop and booklet activities in April 2023. The 14 workshop booklet responses were deductively analysed using Nutbeam’s health literacy hierarchy. Results School  A’s booklet responses showed that interactive health literacy responses were dominant (54%), followed by functional (34%) and critical learning activities (12%), whereas School B’s responses showed that functional health literacy responses were dominant (65%), followed by interactive (28%) and critical (5%). Conclusion The findings show that students in both schools were less likely to engage in critical, compared with functional and interactive health literacy levels. This is an important consideration for future workshops, as well as curriculum and teacher training in Vanuatu, as Vanuatu (and other PICTs) are more susceptible to the effects of climate change and food sustainability issues.. Without a focus on developing critical health literacy knowledge and capabilities throughout the schooling years, this is a missed opportunity to create enabling environments that reduce youth exposures to NCD risk factors.